CLINICAL AND LIQUOR DIFFERENCES IN CASES OF SEROUS AND PURULENT MENINGITIS IN CHILDREN OF DIFFERENT AGE - E. M. Mazayeva; L. A. Alekseyeva; N. V. Skripchenko; T. V. Bessonova (LLC "Diagnostics and Vaccines", 2015)
The article presents features of clinical course and composition of cerebrospinal liquid in cases of purulent and serous meningitis depending on the age of the patients and the disease etiology. 40 children with bacterial purulent meningitis of meningococcal, hemophilic and unknown aetiology and 40 children with serous meningitis predominantly of enteroviral etiology were examined. The differences in duration and intensity of clinical symptoms, total protein concentration, and liquor cytosis were detected. The highest liquor indicators were revealed in the case of hemophilic meningitis in children of early age and in the case of meningococcal meningitis in children over seven years old. This fact can be explained by various pathogenic features of the causative agent and different compensatory reactions in children of different age.